Positive youth development attributes, mental disorder, and problematic online behaviors in adolescents: a longitudinal study amidst the COVID-19 pandemic - Gan, Xiong; Xiang, Guo-Xing; Li, Min; Jin, Xin; Qin, Ke-Nan (Frontiers in Public Health, 2023)
During the COVID-19 pandemic, adolescents have increasingly suffered from online problem behaviors and mental disorders. But little research has paid attention to the protective factors among adolescents. Therefore, the present study attempted to investigate the role of positive youth development (PYD) attributes in adolescents’ depression, internet gaming disorder (IGD) and cyberbullying/victimization (CBV). A total of 995 Chinese adolescents (Mage = 15.97 years, SD = 0.77, 325 boys) from two public high schools in Hubei province were recruited to participate in the three-wave longitudinal study over the span of one year during the pandemic (Time 1: November, 2020; Time 2: May, 2021; Time 3: November, 2021). T1 PYD attributes negatively predicted T2 depression and T3 online problematic behaviors. T2 depression positively predicted IGD at T3. T3 IGD significantly predicted greater involvement in T3 CBV, and vice versa. Moreover, depression and one online problem behavior mediated the relationships between PYD attributes and the other online problem behavior, separately and sequentially. These findings demonstrated the protective role of PYD attributes in prevention of mental disorders and online problem behaviors among adolescents during the COVID-19 pandemic. Comprehensive measures should be taken to assist young people to develop more PYD attributes to promote healthy growth.